Group exercise training for balance, functional status, spasticity, fatigue and quality of life in multiple sclerosis: a randomized controlled trial - Tarakci, Ela; Yeldan, Ipek; Huseyinsinoglu, Burcu E; Zenginler, Yonca; Eraksoy, Mefkure (Clinical rehabilitation, 2013)
Objective: To determine the effectiveness of group exercise training on balance, functional status, spasticity, fatigue and quality of life in patients with multiple sclerosis. Design: A randomized single-blind controlled study. Setting: University hospital, outpatient physical therapy department. Subjects: Ambulatory patients with multiple sclerosis. Interventions: Exercise group completed a 12-week group exercise programme under the physical therapists’ supervision. Control group was included in the waiting list. Main measures: The primary outcome measures were the Berg Balance Scale, 10-metre walk test, 10-steps climbing test and secondary outcome measures were the Modified Ashworth Scale, Fatigue Severity Scale and Multiple Sclerosis International Quality of Life. Results: Ninety-nine patients completed the study. There were statistically significant improvements for all outcome measures in the group exercise group (n = 51) (p < 0.01). In the control group (n = 48), there were statistically significant negative change in the Berg Balance Scale and 10-metre walk test measures (p = 0.002, p = 0.001) and statistically significant increment only in the Fatigue Severity Scale score (p = 0.002). The Berg Balance Scale score was increased 4.33 in the exercise group, while a decreased of 2.33 in control group. The 10-metre walk test duration (second) was decreased 2.72 in exercise group, while increased 1.44 in control group. In comparing inter-groups changes, both primary and secondary outcome mesures showed significant improvements in favour of the exercise group after the training (p < 0.05). Conclusion: The study demonstrated that supervised group exercise training is effective in improving balance, functional status, spasticity, fatigue and quality of life in moderately affected people with multiple sclerosis, with no worsening of their clinical status.